CHARACTERISTIC OF SKIN MORPHOLOGY OF SUNDA PORCUPINE (Hystrix javanica) WITH SPECIAL REFERENCE TO THE CONNECTIVE TISSUE - Andhika Yudha Prawira; Desrayni Hanadhita; Anisa Rahma; Supratikno Supratikno; Savitri Novelina; Srihadi Agung Priyono (Jurnal Kedokteran Hewan, 2018)
This study was conducted to investigate the histological characteristic, type, and distribution of connective tissue in Sunda porcupine skin. The investigation was carried out in three adult of sunda porcupines at microscopic level using hematoxylin eosin, Masson thrichrome, Verhoeffs van Gieson, alcian blue pH 2.5 and periodic acid Schiff staining methods. Skin consists of epidermis, dermis hypodermis, and subcutaneous muscle. Quill follicles were the main and dominant structure as well as the specific characteristic on Sunda porcupine skin. The connective tissue was distributed well in basal membrane, dermis, quill follicle, and hypodermis with various intensity and density. The collagen was the main fiber found in the skin while the elastin fiber was not observed. The acid carbohydrate was found distributed well in the skin while the neutral carbohydrate was not detected in this study. In addition the fibers of connective tissue associated with the adipose tissue which found plentifully in quill follicles and hypodermis. The present results showed that the wide distribution of connective tissue might have an important role on the wound healing physiology of Sunda porcupine skin.